Re-reading Polanyi in times of populism - Ząbkowicz, Anna (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2026)
Review: Christopher Holmes, Polanyi in Times of Populism: Vision and Contradiction in the History of Economic Ideas, Routledge, 2019, pp. 175.